Phylacteries as Metaphor in Elie Wiesel's Le Testament d'un poète juif assassiné - Simon P. Sibelman (Studies in 20th & 21st Century Literature, 1994)
The novels of the Holocaust survivor, Elie Wiesel, were initially read as eloquent expressions of remembrance and witnessing to the massacred millions who perished in Hitler's Inferno. His fiction is likewise a profound expression of Jewishness and of the author's fundamental belief that post-Auschwitz Jewry must draw nearer to its authentic roots. To that end, Wiesel' s novel, Le Testament d'un poète juif assassiné, represents the author's most compelling expression concerning Jewish identity. The novel is replete with the language, symbols and meta-structural techniques which elicit an exhortation to remain faithful to one's Jewishness. Moreover, Wiesel provides the reader a single, subtle metaphoric mise-en-abyme which gathers together all the signs and symbols of Jewishness: the protagonist's phylacteries. This paper will explore the importance of the phylacteries as metaphor as well as analyzing the manner in which they serve as a fil conducteur, linking the novel's various narrative levels and providing the structural cement and symbolic matrix to unify the text.
Keywords: Holocaust survivor; Elie Wiesel; expressions of remembrance; remembrance; Holocaust; expression of Jewishness; Jewishness; post-Auschwitz Jewry; authentic roots; Le Testament d& #x27; un poète juif assassiné; Jewish identity; language; symbols; meta-structural techniques; faith; identity; mise-en-abyme; signs; protagonist& #x27; s phylacteries; phylacteries; metaphor; fil conducteur; narrative levels; narrative